Pengaruh kebijakan dividen, kebijakan hutang dan arus kas terhadap harga saham pada perusahaan LQ 45 - Tantrio, Wendi; Hikmah (LPPM Universitas Putera Batam, 2022)
The survey was conducted among LQ45 companies listed on the Indonesia Stock Exchange (IDX). The survey included 45 LQ companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The sampling method was rational sampling and the sample size was 28 companies. The method used in this research is the logical sampling method. The results of this study show that the significant test for cash flows is 0.05 < 0.002 and the significant test for debt policy is 0.675. > 0.05 From this it can be concluded that the dividend and debt policy has no influence on the share prices of companies that are listed on the Indonesian stock exchange LQ45. Dividend policy, debt policy and cash flow all have a significant impact on share prices and have a significant value of 0.016 liters. 0.05. Second, this study gives a coefficient of determination of 0.073. This means that dividend policy, debt policy, and cash flow affect 7.3% and 92%, respectively, of the company's LQ 45 stock price, and the remaining 7% is an explanation for another variable that was not examined in this study.